Reviews of Books (International review of mission, 1952)
Books Reviewed in this article: THE THEOLOGY OF CULTURE: Christ and Culture. By H. Richard Niebuhr. THE SCIENCE OF MISSIONS: P. Robert Streit, o.m.i., ein Pionier der katholischen Missionswissenschaft. By Johannes Pietsch, o.m.i. THE SCIENCE OF MISSIONS: Introduction à la Missiologie. By André V. Seumois, o.m.i. GESTURES AND ATTITUDES IN PRAYER: Die Gebetsgebärden der Völker und das Christentum. By Thomas Ohm, o.s.b. WOMEN IN THE CHURCH: The Service and Status of Women in the Churches. By Kathleen Bliss. ANGLICAN MISSIONS AND THE EPISCOPATE: Bishops and Societies: A study of Anglican Colonial and Missionary Expansion, 1698–1850. By Hans Cnattingius. THE GOSPEL IN THE LANGUAGE OF MODERN MAN: The Communication of the Gospel. By David H. C. Read. THEOLOGY FOR THE LAYMAN: Foundations of Christian Teaching (Základy učení krest'anského). By M. Bič, J. L. Hromadka, R. Říčan, J. B. Souček THE BIBLE TRANSLATORS' CHRISTIAN MINISTRY: God's Word in Man's Language. By Eugene A. Nida. THE CHURCH AND THE HEALING ART: The Church and Healing. By Carl J. Scherzer. A PORTRAIT: Father Douglass of Behala. By Some of his Friends. PEOPLES AND CULTURES: Notes and Queries on Anthropology. Sixth Edition, revised and rewritten by a committee of the Royal Anthropological Institute of Great Britain and Ireland THE MEETING OF EAST AND WEST: Near East Culture and Society: A Symposium on the Meeting of East and West. Edited by T. Cuyler Young. INTRODUCTION TO AFRICA: This is Africa. By Franklin Mack. INTRODUCTION TO AFRICA: Africans on Safari. By Leslie C. Sayre. INTRODUCTION TO AFRICA: Jungles Ahead. By Esther D. Horner. INTRODUCTION TO AFRICA: African Heritage. By Emory Ross. INTRODUCTION TO AFRICA: Introduction to Africa: A selective guide to background reading. Prepared in the Library of Congress by Helen F. Conover under the direction of Harry J. Krould.